Floral Calendar of Honeybee Plants in Kellem and West Wollega Zone, Western Ethiopia - Ofijan Tesfaye; Etenesh Mekonnen (International Journal of Forestry Research)
Beekeeping has significantly contributed to environmental conservation and the preservation of natural resources. Although the quality and quantity of flora available play a major role in the success of the sector, the botanical makeup of natural vegetation varies greatly. This study was conducted targeting the identification and documentation of major honeybee floras and their flowering calendar. Midland and lowland agroecologies were purposively selected. Continuous field plant registration was performed. Melissopalynological analysis from bee pollen and honey were used to identify floral origin. Field observations identified 59 and 63 plants in the midland and lowlands, respectively. Season 1 had the highest pollen yields, ranging from 11051.8 ± 56.4 g (midlands) to 878.3 ± 18.3 g (lowlands), while season 4 ranged from 16.8 ± 6.3 g (midlands) to 15.6 ± 7.4 g (lowlands) and had the lowest pollen yield. In both regions, February, March, July, and August are the months when pollen is not brought into the hive and could be used as starvation periods. A total of 1430.8 ± 75.4 and 1291.8 ± 71.4 g of bee pollen/hive were collected throughout the year in midland and lowland, respectively, and Asteraceae was the richest family accounting around 90% of pollen weight. In both agroecologies, honey is harvested three times a year. In the midland, monofloral honey, namely, Guizotia spp (64.42%) and Croton macrostychus (47.42%), was harvested in November and May, respectively, while honey harvested in February was multifloral type. Similarly, in the lowlands, monofloral honey of Guizotia spp (51.85%), Coffee arabica (55.22%), and Croton macrostychus (50.42%) was harvested in December, March, and June, respectively. Based on the results, Bidens prestinaria, Bidens pilosa, Guizotia spp, C. macrostachyus, Eucalyptus spp, Lepidium sativum, Zea mays, Hypostes trifolia, Vernonia spp, Trifolium spp, Helianthus annuus, C. arabica, Brassica abyssinica, Andropogon abyssinicus, Sorghum bicolor, Cordia africana, Syzygium guineense, and Terminalia spp are major bee plants. It is found that the study area is rich in bee plant diversity and hence has a potential for honey production.